2009
DOI: 10.1111/j.1399-5448.2008.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Missed bolus doses: devastating for metabolic control in CSII-treated adolescents with type 1 diabetes

Abstract: Objective: To investigate the management of continuous subcutaneous insulin infusion (CSII) in adolescents with type 1 diabetes including their administration of bolus doses and to study relationships between insulin omission and metabolic control, body mass index, daily frequency of selfmonitoring of blood glucose (SMBG) and bolus doses, health-related quality of life (HRQOL), the burden of diabetes and treatment satisfaction. Methods: Ninety CSII-treated (!6 months) adolescents aged 12-18 yr, from four diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 24 publications
7
98
1
2
Order By: Relevance
“…11-13 Burdick et al 11 determined that youths who missed at least one mealtime bolus per week had an average HbA1c level that was 0.8% higher than youths who did not miss any mealtime boluses. Likewise, Olinder et al 12 reported average HbA1c levels 0.8% higher for youths who missed mealtime insulin boluses compared with youths who did not miss mealtime boluses, and another study found youths who skipped mealtime insulin boluses had an average HbA1c of 8.67%. 13 There is also a study showing that missed snack time insulin boluses may be common for some youth with type 1 diabetes and related to daily episodes of glycemic excursion.…”
Section: Discussionmentioning
confidence: 98%
“…11-13 Burdick et al 11 determined that youths who missed at least one mealtime bolus per week had an average HbA1c level that was 0.8% higher than youths who did not miss any mealtime boluses. Likewise, Olinder et al 12 reported average HbA1c levels 0.8% higher for youths who missed mealtime insulin boluses compared with youths who did not miss mealtime boluses, and another study found youths who skipped mealtime insulin boluses had an average HbA1c of 8.67%. 13 There is also a study showing that missed snack time insulin boluses may be common for some youth with type 1 diabetes and related to daily episodes of glycemic excursion.…”
Section: Discussionmentioning
confidence: 98%
“…This procedure prevents the reduction of comfort and quality of life, and minimizes the risk of negligence in the form of avoidance of boluses or lack of self-control, which may lead to worse metabolic control of diabetes [60][61][62]. According to the opinion of the American Diabetes Association (ADA) education should be provided in calculating the amount of carbohydrates in consumed meals [63].…”
Section: Protein and Fat Exchangesmentioning
confidence: 99%
“…In some situations, the parent and paediatric diabetes team have to provide time-consuming training sessions for school staff before allowing a young child using an insulin pump to attend school. When adolescents use pump therapy, it is not uncommon for them to forget to administer bolus insulin before/after eating a meal (27). Besides, children and adolescents tend to eat irregularly, and missed bolus insulin doses may counterbalance the advantage of the basal insulin replacement offered by CSII (25).…”
Section: Insulin Pumpsmentioning
confidence: 99%
“…The level and need for self-care also differs with age; children with diabetes who were diagnosed at an older age have been reported to have more success with self-care (22). The consequences of forgetting or omitting doses of insulin may lead to a deterioration of metabolic control and include increasing levels of haemoglobin (Hb)A1c (26,27), which lead to an increased risk of diabetes-related complications. There is a need to improve self-care in children and adolescents as long-term poor metabolic control will increase the risk of diabetic complications and cardiovascular disease (28,29).…”
Section: Use Of Insulin Pens In the Paediatric Populationmentioning
confidence: 99%